Down-regulation of claudin-18 is associated with the proliferative and invasive potential of gastric cancer at the invasive front. - Tadayuki Oshima; Jing Shan; Takuya Okugawa; Xin Chen; Kazutoshi Hori; Toshihiko Tomita; Hirokazu Fukui; Jiro Watari; Hiroto Miwa (PLoS ONE, 2013)
BACKGROUND: Claudins are known as tight junction proteins, and their expression pattern in gastric cancer is still controversial. The relationship between the expression patterns of tight junction proteins and tumor proliferation in early gastric cancer is still far from clear. AIMS: To investigate the expression patterns of claudin-18 and Ki-67 in early gastric cancer at the invasive front and surrounding normal gastric mucosa and to investigate the biological function of claudin-18 in the proliferation and invasion of cancer cells. METHODS: Seventy-five early gastric cancer lesions removed via endoscopic mucosal resection or endoscopic submucosal resection were evaluated. All gastric cancer lesions were diagnosed as differentiated adenocarcinoma using the Japanese Classification of Gastric Carcinoma. To assess epithelial proliferation, immunostaining with Ki-67 was performed, and the labeling index was calculated. To assess the expression of epithelial tight junction proteins, immunofluorescent staining of claudin-18 was performed. The immunoreactivity of claudin-18 was graded according to the number of stained cells. Correlation analysis was performed by Spearman's rank correlation coefficient. Transfection of claudin-18 small interfering RNA (siRNA) was accomplished in MKN74, a claudin-18-positive gastric cancer cell line, to investigate the effect of claudin-18 on proliferation and invasion of cancer cells. RESULTS: Claudin-18 was significantly down-regulated in gastric cancer compared to surrounding gastric normal mucosa or intestinal metaplasia. The Ki-67 labeling index of gastric cancer at the invasive front was inversely correlated with the claudin-18 level, but that at the mucosal lesion was not correlated. Claudin-18 knockdown significantly promoted the proliferation of MKN74 compared with control siRNA-transfected cells. MKN74 invasion increased significantly with claudin-18 siRNA transfection compared with control siRNA transfection. CONCLUSIONS: Down-regulation of claudin-18 is associated with the proliferative potential at the invasive front of gastric cancer, suggesting that it has a pivotal role in gastric cancer progression.